Świadczenia socjalno-bytowe zakładów pracy na rzecz pracowników i ich rodzili - Piasny, Janusz (Wydział Prawa i Administracji UAM, 1985)
The evolution and assesment of functioning of a system of employers' social benefits for workers and their families is a subject of the discussion in the article. The following social benefits are mily vacations, holiday's rest and tourism, rest of children and youth, maintaining cultural and educational units, and a developement of a phisical culture and sports. Those forms of services are aiming at securing proper conditions for workers and their families to reproduce working force in the leisure time. The second group of services is the benefits related directly to forming work conditions of persons employed in a given enterprise. Those benefits include subsiding enterprise housing, workers' lodging houses, private rooms, collective catering, schooling and medical services attached to an institution. The article presents not only changes in the scope of formation and distribution of benefits but also indicates at the previous failures of their functioning and at the ways and possibilities of their overcoming in the future.
Social benefits of employers for employes and their families